Smart Toolkit for Evaluating Information Projects, Products and Services: Second Edition: Part I Evaluation Context - Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture; Royal Tropical Institute (Technical Centre for Agricultural and Rural Cooperation, 2009)
In Part 1, we start by providing some background to monitoring, evaluation and impact assessment, what the terms mean, and recent changes in approach.